(untitled) (Bangladesh Journal of Animal Science, 2013)
The aim of this study was to know the effects of postpartum re-mating intervals on reproductive performances of does and growth of kits. Fifteen female New Zealand White crossbred rabbits were divided into three groups of equal numbers. They were re-mated within 24 hours, at 10 days and 28 days postpartum. Animals were individually caged in cells measuring 2’×2’×2’. Does were kept under natural lighting. Plastic nest boxes were supplied to does 3-4 days before parturition. They were reared up to four generation. Litter weight at birth was significantly (p<0.05) higher at 10 days postpartum than within 24 hours and at 28 days postpartum intervals. Higher growth rate was observed in 10 days postpartum group comparing to other re-mating groups. Milk yield of the dams were significantly (p<0.05) higher when dam re-mated at 10 days postpartum than those re-mated within 24 hours after parturition. Conception rate, gestation length of does, litter size at birth and weaning, litter weight at weaning, doe weight at mating, kidding, weaning and kid mortality did not differ significantly among the groups. Rabbit does re-mated at 10 days postpartum show maximum litter weight at birth, growth rate of kits and milk yield of dam. DOI: http://dx.doi.org/10.3329/bjas.v42i2.18497 Bang. J. Anim. Sci. 2013. 42 (2): 143-147